Capacity-strengthening pathways enabling agroecological transition in Vietnam’s rice sector - Minh, Thai Thi; Tran, Dinh Thi; Dubois, Mark; Bergamini, Nadia; Mockshell, Jonathan (2024)
Agroecological approaches are increasingly promoted for food systems transformation by applying ecological principles, regeneratively using natural resources and ecosystem services, and addressing the need for socially equitable food systems. Yet, despite widespread support from social movements, agroecological transition (AET) is still constrained by a lack of holistic performance metrics, top-down incentives and investments, and limited capacity to engage with private-public finance models, businesses, and policy processes. Large-scale AET requires empowering diverse actors and organizations to exercise their choices and roles to develop individual and institutional capability pipelines to create and harness opportunities for new businesses to capture more value from agriculture and food systems.